KORELASI CLASS ATTENDANCE DENGAN NILAI PERKULIAHAN: SUATU STUDI DI UIN AR-RANIRY - Azharsyah Ibrahim (Jurnal Pencerahan, 2015)
This study was motivated by the polemic on the importance of class attendance in a learning process in the institutions of higher education. This article aims to examine the influence of class attendance on students’ grades using quantitative approach. Primary data was collected from four classes of Department of Islamic Banking Diploma (D-III PS) and Department of Islamic Economics of State Islamic University (UIN) Ar-Raniry, Banda Aceh. Data was then analysed using several stastistical techniques from the SPSS. The result showed that statistically there was a significant positive correlation between class attendance and students’ grades. The findings clearly demonstrated the importance of class attendance in attaining the good grades among university students within the two departments. Nevertheless, analyzing the results more closely indicated that class attendance was not a direct factor in enhancing the students’ grades. It only functioned as a mediator and trigger for the emergence of other factors, i.e. motivation, persistence, and cognitive ability